2020
DOI: 10.13057/biodiv/d210648
|View full text |Cite
|
Sign up to set email alerts
|

Potential antagonistic rhizobacteria to control Colletotrichum scovillei, the cause of anthracnose disease in chili pepper

Abstract: Abstract. Darmadi AAK, Suprapta DN, Khalimi K. 2020. Potential antagonistic rhizobacteria to control Colletotrichum scovillei, the cause of anthracnose disease in chili pepper. Biodiversitas 21: 2727-2734. Six species of Colletotrichum were identified as the cause of anthracnose disease on Bali Island, Indonesia in 2018. These species were C. scovillei, C. acutatum, C. nymphaeae, C. gloesporioides, C. truncatum, and C. fructicola. Among them, C. scovillei was the most prevalent at 55% of all samples tested. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In our previous study we detected three compounds in the cell-free filtrate of P. polymixa C1: 3-hydroxy-2-butanone, 2, 3-Butanediol, and 2, 3-Butanediol (Darmadi et al, 2020). Other researchers proved that 3-hydroxy-2-butanone is a volatile compound with antifungal activity (Lim et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous study we detected three compounds in the cell-free filtrate of P. polymixa C1: 3-hydroxy-2-butanone, 2, 3-Butanediol, and 2, 3-Butanediol (Darmadi et al, 2020). Other researchers proved that 3-hydroxy-2-butanone is a volatile compound with antifungal activity (Lim et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Scanning electron microscopy showed that serious damage on the mycelia of C. scovillei was observed. Wrinkles were observed on the mycelia of C. scovillei grown side by side with P. polymyxa C1, whereas no such wrinkle was observed on C. scovillei grown alone (Darmadi et al, 2020). A study done by Shahbazi et al (2014) showed that antagonistic Streptomyces rochei strain P14 caused hyphal tip lyses, folding back, stunted mycelium, disintegrated hyphae, and curling of hyphae on Colletotrichum, the cause of anthracnose on chili pepper.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The crudes extract with HOCl was more potent agains Fusarium spp. Other study also found the methanolic P. betel extract also act against Fusarium oxysporu f.sp vanilla at MIC 3000 µg/ml [43] Recently, Fusarium spp. has emerged as one of the most concerned fungi as it is not just a soil pathogen, but the Fusarium conidia can be disseminated by water in rain splashes and irrigation systems, and have the ability to become airborne when dried, leaving them well-suited for long-distance atmospheric dissemination and contributing to global concern [44].…”
Section: Mic and Mfc Resultsmentioning
confidence: 89%
“…Similar results were reported bySundaramoorthy et al (2012) wherein the synthesis of phytolaexins by Bacillus subtilis induced systemic resistance against wilt disease caused by Fusarium solani in chilli. Cell free supernatant of Paenibacillus polymyxa containing 3-hydroxy-2-butanone and 2,3-butanediol showed wrinkles on mycelia of Colletotrichum scovillei which causes anthracnose in chilli(Suprapta et al 2020). Antimicrobial compound Phenazine-1-carboxamide produced by Pseudomonas aeruginosa showed deformation of mycelia and inhibition of sporulation thus inhibiting the growth of fungal pathogen Colletotrichum capsici causative agent of fruit rot in chilli(Kumar et al 2005).…”
mentioning
confidence: 99%